Behaviour of Listeria Monocytogenes in Pasteurization Milk during Refrigerator Storage - Syahriana Sabil, Ratmawati Malaka; Prahesti, Kusumandari Indah; Yuliati, Farida Nur (European Journal of Sustainable Development, 2019)
Milk is an excellent medium for the growth of microorganisms including Listeria monocytogenes. Some pathogenic bacteria can survive after pasteurization in milk, and these bacteria can contaminate again after storage. The purpose of this study was to determine the behavior of L. monocyogenes after pasteurization in refrigerator storage. Fresh milk is pasteurized at 75, 80, 85, 90 and 95 ° C for 1 minute and stored at refrigerator temperature for 1 day, 1 week and 2 weeks. Characteristics of growth and total number of L. monocytogenes in Listeria Selective agar Base medium were observed. The results showed that the total number of L. monocytogenes at the control temperature before pasteurization was 7.91 (log cfu / ml). At pasteurization temperatures of 75, 80 and 85 ° C for 1 min, the number of L. monocytogenes bacteria were decrease to 5.83, 3.82 and 1.18 (log cfu / ml), respectively, whereas the total numbers of this bacteria on pasteurization temperatures of 90 and 95 C were all listeria killed, but can grow back in refrigerator storage (4°C). Keywords: Pasteurization, milk, Listeria monocytogenes, refrigerator storage